Penguatan Berpikir Kritis Siswa Menengah Atas melalui Kasus Intoleransi dalam Projek P5 - Safitri, Syaila Salsabila; R, Resti; Rachman, Ichsan Fauzi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Critical thinking is an essential skill for students in dealing with a digital age filled with information that is not necessarily accurate. This article examined how the Pancasila Student Profile Reinforcing (P5) contributes to improved high school students' critical thinking ability through project-based learning, particularly in the face of intolerance in the educational environment. Using library study methods, the study highlights the relationship between critical thinking, global literacy, and student charactering efforts according to pancasila values. The results suggest that a P5 based approach can foster tolerance attitudes and increase student social awareness in understanding the various perspectives in society. This article recommends implementing a more integrational learning strategy to support critical understanding and strengthen national value in Indonesian education.